Socialization and inequality: a biographical approach to the working class in Portugal - Abrantes, P. (2016)
his article discusses the relationship between socialization and inequality, exploring the case of the working class in Portugal. Bringing together different sociologic traditions, the framework draws upon Bourdieu’s concepts of habitus and practices, balanced with recent research on life histories, globalization and individualization. The life stories of 52 workers produced in the context of an adult education programme are analysed, focusing on two major topics: life pathways and class trajectories, and subjectivity, identity and values (stressing the weak class consciousness). The article discusses the potentialities/challenges of using the biographical method to study socialization and inequalities, particularly when developed in educational contexts. According to the analysis, life pathways are often branded by temporary rural, industrial and services work experiences, crossed by ‘turning points’ and dramatic moments, though with some generational and gender differences. Classes are seldom referred to, but narratives are framed by key socialization institutions (work, family, local community, church, army) and a sense of deficit, pride and shame, linked to the inequalities structure. Although a pervasive economic, cultural and political change from the 1960s on is evident, our research found key features of a working-class habitus, rooted in specific life paths and socialization institutions. These are likely to be stretched in the current context of economic crisis and neoliberal policies in southern Europe.